The Criminal Responsibility Against Persons of The Crime of Embezation in Office - Subandi, Subandi; Winjaya Laksana, Andri (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2024)
The crime of embezzlement in office is regulated in Article 374 of the Criminal Code. The crime of embezzlement in office is a crime of embezzlement with aggravation. The aim of this research is to find out and analyze the criminal liability of perpetrators of criminal acts of embezzlement in office; and knowing and analyzing regulations against perpetrators of criminal acts of embezzlement in office in the future. This legal research uses an empirical legal research approach. The research results show that even though the perpetrator has returned the company money he used, it does not rule out the possibility that the victim as the company owner will still bring a case and submit it to court. However, the law must still be enforced because the perpetrator did make a mistake. Regulations against perpetrators of criminal acts of embezzlement in office in the future, apart from using penal measures, also use non-penal measures. The non-penal efforts undertaken should be realized in strategic activities, both socially, economically and legally, so that criminal acts of embezzlement in office can be minimized from an early age.